Cultivating Islamic Religious Traditions, Spirituality, and Social Harmony: A Mixed-Methods Study of KH. Noer Alie’s Legacy in Bekasi, Indonesia - Hunaidah Hunaidah; Mawaddah Warohmah; Aca Syathybie (International Journal of Nusantara Islam, 2026)
This study examines how the development of Islamic religious traditions contributes to spirituality and social harmony, with a focus on the legacy of KH. Noer Alie in Bekasi, Indonesia. Previous research has examined Islamic ritual practices and community cohesion. This study aims to analyze the role of religious traditions in nurturing individual and communal spirituality, evaluate their contribution to social harmony, and clarify their implications for Islamic religious education and community-based da'wah management. A convergent mixed-methods design was used, combining survey data with interviews, focus group discussions, and document analysis. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis and integrated to generate shared interpretations. The findings indicate that the development of religious traditions inspired by Noer Alie, particularly the haul (ḥaul), maulid (mawlīd), tahlil (tahlil), the Nisfu Sha'ban (Middle-Month of Sha'ban) celebration, and the ketupat giving, strengthens spirituality and social harmony by instilling Islamic ethical values ​​into communal rituals and intergenerational institutional practices. This study concludes that this tradition-based da'wah model offers a theoretically grounded and implementable framework for Islamic education, Islamic boarding schools (pesantren), majelis taklim (Islamic study groups), and policies aimed at building social cohesion.